1, 3-Propanediol production from glycerol with a novel biocatalyst Shimwellia blattae ATCC 33430: Operational conditions and kinetics in batch cultivations. (January 2016) - Rodriguez, Alberto; Wojtusik, Mateusz; Ripoll, Vanessa; Santos, Victoria E.; Garcia-Ochoa, F.
Graphical abstract: Highlights: Shimwellia blattae, a wild type risk class 1 bacterium, produces 1, 3-propanediol (PDO). The influence of temperature, pH and fluid dynamic conditions is determined. PDO production is not affected for the use of crude glycerol as raw material. Yield and productivity values are in line with published data from risk class 2 strains. Abstract: Shimwellia blattae ATCC 33430 as biocatalyst in the conversion of 1, 3-propanediol from glycerol is herein evaluated. Several operational conditions in batch cultivations, employing pure and raw glycerol as sole carbon source, were studied. Temperature was studied at shaken bottle scale, while pH control strategy, together with the influence of raw glycerol and its impurities during fermentation were studied employing a 2 L STBR. Thereafter, fluid dynamic conditions were considered by changing the stirring speed and the gas supply (air or nitrogen) in the same scale-up experiments. The best results were obtained at a temperature of 37 °C, an agitation rate of 200 rpm, with free pH evolution from 6.9 and subsequent control at 6.5 and no gas supply during the fermentation, employing an initial concentration of 30 g/L of raw glycerol. Under these conditions, the biocatalyst is competitive, leading to results in line with other previous works in the literature in batch conditions, reaching a final concentration of 1, 3-propanediol of 13.84 g/L, with a yield of 0.45 g/g and a productivity of 1.19 g/(L h) from raw glycerol.